Disparities in Oral Cancer Survival among Mentally Ill Patients - Chang, Ting-Shou; Hou, Szu-Jen; Su, Yu-Chieh; Chen, Li-Fu; Ho, Hsu-Chieh; Lee, Moon-Sing; Lin, Chun-Hsuan; Chou, Pesus; Lee, Ching-Chih (PLOS ONE, 2013)
Background Many studies have reported excess cancer mortality in patients with mental illness. However, scant studies evaluated the differences in cancer treatment and its impact on survival rates among mentally ill patients. Oral cancer is one of the ten most common cancers in the world. We investigated differences in treatment type and survival rates between oral cancer patients with mental illness and without mental illness. Methods Using the National Health Insurance (NHI) database, we compared the type of treatment and survival rates in 16687 oral cancer patients from 2002 to 2006. The utilization rate of surgery for oral cancer was compared between patients with mental illness and without mental illness using logistic regression. The Cox proportional hazards model was used for survival analysis. Results Oral cancer patients with mental disorder conferred a grave prognosis, compared with patients without mental illness (hazard ratios [HR] = 1.58; 95% confidence interval [CI] = 1.30–1.93; P<0.001). After adjusting for patients’ characteristics and hospital characteristics, patients with mental illness were less likely to receive surgery with or without adjuvant therapy (odds ratio [OR] = 0.47; 95% CI = 0.34–0.65; P<0.001). In multivariate analysis, oral cancer patients with mental illness carried a 1.58-times risk of death (95% CI = 1.30–1.93; P<0.001). Conclusions Oral cancer patients with mental illness were less likely to undergo surgery with or without adjuvant therapy than those without mental illness. Patients with mental illness have a poor prognosis compared to those without mental illness. To reduce disparities in physical health, public health strategies and welfare policies must continue to focus on this vulnerable group.